2002
DOI: 10.1007/s00203-002-0430-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel streptomycete lipase: cloning, sequencing and high-level expression of the Streptomyces rimosus GDS(L)-lipase gene

Abstract: An extracellular lipase from Streptomyces rimosus R6-554W has been recently purified and biochemically characterized. In this report the cloning, sequencing, and high-level expression of its gene is described. The cloned DNA contained an ORF of 804 bp encoding a 268-amino-acid polypeptide with 34 amino acid residues at the amino terminus of the sequence that were not found in the mature protein. The theoretical molecular mass (24.172 kDa) deduced from the amino acid sequence of the mature enzyme was experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…The amino acid sequence showed 268 amino acid residues, including 34 of the signal peptide (TrEMBL accession number Q93MW7). 21 The enzyme contains six cysteines. All of them were shown to form intramolecular disulfide bonds (C-27-C-52, C-93-C-101 and C-151-C-198) and therefore contribute to the observed high stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid sequence showed 268 amino acid residues, including 34 of the signal peptide (TrEMBL accession number Q93MW7). 21 The enzyme contains six cysteines. All of them were shown to form intramolecular disulfide bonds (C-27-C-52, C-93-C-101 and C-151-C-198) and therefore contribute to the observed high stability.…”
Section: Introductionmentioning
confidence: 99%
“…20 In order to explore biotechnological applications and to characterize the structure on the protein level, large quantities of enzyme are required. Therefore, cloning, sequencing and high-level expression of S. rimosus lipase gene was carried out, 21 and the derived nucleotide sequence was analyzed by bioinformatic approaches. 21,22 Recently, capillary electrophoresis-on-a-chip, matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) and matrix-assisted laser desorption/ionization quadrupole ion trap reflection time-of-flight (MALDI-QIT-RTOF) mass spectrometry were used to characterize the primary structure of the S. rimosus lipase at the protein level and to prove the identity of the lipase from the wild-type and the overexpressing strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpressed lipase was purified from culture filtrate of S. rimosus strain R6-ZGL3(pDJ7) that contains a high-copy-number plasmid harboring S. rimosus lipase gene 35 , as already described 36 . The purity of prepared enzyme solution was confirmed by capillary gel electrophoresis using lab-on-a-chip technology (Agilent Technologies).…”
Section: Enzyme Purificationmentioning
confidence: 99%
“…More recently, it has been shown that two hydrolases from Acidovorax delafieldii and Thermobifida fusca capable of degrading synthetic polyesters exhibit high levels of similarity to these Streptomyces lipases (13,29). Other lipase-encoding genes have been cloned from Streptomyces species, including the gene for a Streptomyces cinnamomeus lipase related to Pseudomonas lipases (26) and a Streptomyces rimosus gene encoding an enzyme representing a third lipase family of Streptomyces (31).…”
mentioning
confidence: 99%